Cognitive performances and DAT imaging in early Parkinson's disease with mild cognitive impairment: a preliminary study. (3rd February 2015) - Pellecchia, M. T.; Picillo, M.; Santangelo, G.; Longo, K.; Moccia, M.; Erro, R.; Amboni, M.; Vitale, C.; Vicidomini, C.; Salvatore, M.; Barone, P.; Pappatà, S.
<x xml:space="preserve">Abstract</x> Objectives Mild cognitive impairment (MCI) is a common feature in Parkinson's disease (PD). We performed an exploratory study to investigate dopaminergic nigrostriatal innervation and its cognitive correlates in early untreated PD patients with MCI as compared to cognitively intact patients. Patients and methods A consecutive series of 34‐de‐novo, drug‐naïve patients with PD were enrolled. They underwent [123‐I] FP‐CIT SPECT and comprehensive neuropsychological battery. MCI was identified in 15 of 34 patients with PD. Results The two groups did not show any statistically significant difference in age, sex, disease duration, education, lateralization, and H&Y and Hospital Anxiety and Depression Scale scores. Logistic regression analysis showed that UPDRS‐III was weakly associated with MCI (P = 0.034). Partial correlation analysis controlling for UPDRS‐III and age suggested that in PD patients with MCI reduced V3″ values in the more affected caudate were correlated with reduced performances in frontal assessment battery, Trail Making Test: part B minus Part A and copy task of the Rey–Osterrieth complex figure test. Reduced V3″ values in the more and less affected putamen were significantly related with reduced performance in frontal assessment battery and in copy task of Rey–Osterrieth complex figure test, respectively. No correlation was found between neuropsychological scores and DAT availability in PD patients without MCI. Conclusions Although preliminary, our results suggest that striatal dopamine depletion may contribute to some cognitive deficit in early never treated PD patients with MCI.